Kinematic and Dynamics Modeling of Nonholonomic Mobile Robot - Jasiński, Krzysztof; Murawski, Lech; Szeleziński, Adam; Kluczyk, Marcin (Scientific Journal of Gdynia Maritime University, 2023)
This paper presents computer simulation results of kinematic and dynamic of two and three – wheeled mobile robot, conducted in the Matlab&Simulink packet environment. Models of kinematics and dynamics were developed with the aid of Jacobians and Lagrange II multiplayers equations.